Bridging smiles: AI-driven dental health awareness for the next gen—a systematic review - Sharma, Pratyasha; Das, Sayan; Bhandary, Srikala; Nayak, Prajna P. (Frontiers in Dental Medicine, 2025)
BackgroundThis systematic review aims to evaluate the effectiveness of mobile applications in improving oral health knowledge, oral hygiene behaviours, plaque, and gingival indices in children.MethodsThe inclusion criteria were defined using the PICOS framework. The population (P) comprised children aged 4–16 years. The intervention (I) included studies utilizing game-based teaching methods for oral health education, such as serious games, interactive games, or other digital and non-digital educational games. Comparators (C) involved alternative interventions, conventional teaching approaches, or control conditions. Eligible outcomes (O) included measures of oral hygiene behaviours, plaque and gingival indices. 5 Randomized controlled trials, 3 pilot studies and 1 cross-sectional study were considered for inclusion after going through a total of 163 articles. Reviews and usability test articles were excluded from the study. A systematic search was completed using keywords alongside thesaurus and MeSH terms on PubMed, Scopus, Cochrane Library and Web of Science databases from 2015 to 2025. This review was conducted by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) checklist, using the specified inclusion and exclusion criteria. The Risk of Bias was assessed using the QUADAS-2 tool. All results were analyzed and summarized into general and specific categories.ResultsNine randomized controlled trials involving children aged 2–19 years were included. Mobile applications used ranged from brushing timers and virtual games to educational videos and messaging platforms. Most interventions reported improvements in oral health knowledge, hygiene behaviours, and plaque reduction. Significant clinical improvements were observed in several studies, particularly those incorporating gamification or theory-based behavioural strategies.DiscussionMobile-based interventions showed promising results in enhancing oral health outcomes among children. Gamified and interactive applications were especially effective in increasing motivation and engagement. However, findings varied across studies, with some reporting comparable or superior outcomes in control groups receiving conventional education. Parental involvement and age-specific tailoring appeared to influence intervention effectiveness.ConclusionMobile health applications have the potential to support pediatric oral health promotion through improved knowledge, behaviour, and clinical outcomes. While the evidence is encouraging, further standardized, high-quality research is needed to confirm long-term effectiveness and guide widespread implementation.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/search, PROSPERO CRD420251065550.